2021
DOI: 10.1620/tjem.254.189
|View full text |Cite
|
Sign up to set email alerts
|

Circular RNA circ_0046264 Suppresses Osteosarcoma Progression via microRNA-940/Secreted Frizzled Related Protein 1 Axis

Abstract: Circular RNAs (circRNAs) feature prominently in regulating tumor progression. The study aims to investigate the role and mechanism of circ_0046264 in osteosarcoma. In this study, dysregulated circRNAs in osteosarcoma tissues and adjacent tissues were screened out by analyzing circRNA microarray (GSE140256). The expressions of circ_0046264 in 58 osteosarcoma tissues and 4 osteosarcoma cell lines were detected by quantitative real-time polymerase chain reaction. Subsequently, the relationship of circ_0046264 exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…circ_0046264 suppresses OS cell progression via targeting miR-940/secreted frizzled-correlated protein 1 gene axis. [ 7 ] In this study, the role of circ-RANGAP1 was probed. circ-RANGAP1 expression is augmented in gastric cancer patients and has the ability to modulate invasion and metastasis of gastric cancer cells via miR-877-3p/vascular endothelial growth factor-A (VEGFA) axis [ 8 ], but its biological function in OS is yet unknown.…”
Section: Introductionmentioning
confidence: 99%
“…circ_0046264 suppresses OS cell progression via targeting miR-940/secreted frizzled-correlated protein 1 gene axis. [ 7 ] In this study, the role of circ-RANGAP1 was probed. circ-RANGAP1 expression is augmented in gastric cancer patients and has the ability to modulate invasion and metastasis of gastric cancer cells via miR-877-3p/vascular endothelial growth factor-A (VEGFA) axis [ 8 ], but its biological function in OS is yet unknown.…”
Section: Introductionmentioning
confidence: 99%
“…This suggests that miR-1197 may be a risk factor for expediting the carcinogenicity of OS cells. CircRNA-miRNA crosstalk has crucial regulatory effects on the onset and development of OS [27,28,29]. miR-1197 has been confirmed to be modulated by circ_0075542 [30], circ_0004018 [31], and circ_0000429 [32] to affect the progression of various cancers except for OS.…”
Section: Circ_0049271 Overexpression Abates Thementioning
confidence: 98%
“…miRNAs, such as miR-421 [24], miR-487a [25], and miR-628-5p [26], are overexpressed in OS and considered as oncogenes for OS progression. Moreover, regulatory mechanisms of various circRNA-miRNA networks, such as circ_0046264-miR-940 [27], circ_0000527-miR-646 [28], and circ_0001721-miR-372-3p [29], have been widely investigated in the occurrence and progression of OS. miR-1197 interacts with circRNAs in several human cancers, including circ_0075542 in prostate cancer (PC) [30], circ_0004018 in hepatocellular carcinoma (HCC) [31], and circ_0000429 in NSCLC [32].…”
mentioning
confidence: 99%
“…Du and colleagues, demonstrated that SFRP1, that is known to inhibit the proliferation, migration and invasion of OS cells by inhibiting Wnt/β-catenin signaling [ 384 ], is upregulated in OS cells overexpressing circ_0046264. Mechanistically, circ_0046264 can upregulate SFRP1 expression by sponging miR-940 [ 300 ]. The tumor-suppressive role of circ_0046264 was also demonstrated in lung cancer where it can inhibit viability, invasion, and induce apoptosis by upregulating BRCA2 expression through down-regulating miR-1245 [ 385 ].…”
Section: Cernets Involving Circrnasmentioning
confidence: 99%